Molecular detection of pathogenic bacteria in Rhipicephalus sanguineus (sensu lato) ticks from Bitung, North Sulawesi, Indonesia - JANE TAHULENDING; MAX TULUNG; JANTJE PELEALU; DIANA VANDA DODA (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Tahulending J, Tulung M, Pelealu J, Doda DV. 2022. Molecular detection of pathogenic bacteria in Rhipicephalus sanguineus (sensu lato) ticks from Bitung, North Sulawesi, Indonesia. Biodiversitas 23: 6164-6170. Domesticated dog populations have grown throughout Indonesia, notably in Bitung City. Dogs are frequently kept as home guardians and reside with their owners. Dogs are typically attacked by ectoparasites, parasites that adhere to the skin's surface and potentially spread the disease microorganisms to humans, animals, and the environment. As a specific host, ticks are frequently found in dogs. This research aims to identify and analyze the molecular character bacterial of Rhipicephalus sanguineus ticks in Bitung City. A hypervariable region of 16S rRNA called V3-V4 was selected for the DNA barcode area. Dogs' ticks have been collected from several areas in Bitung. The microbes inside the digestive tract were analyzed using genomic DNA with a gSYNC DNA extraction kit, and PCR amplification using KOD FX Neo and MyTaq HS red mix. At First Base Singapore, gel electrophoresis and sequencing were carried out. The collected sequencing data were analyzed using MEGA X and the BLAST, connected online with the NCBI's GenBank. The nine distinct bacteria were identified inside the digestive tract of ticks. Pseudomonas stutzeri (35%), Brevundimonas sp. (21%), and Aquamicrobium lusatiense (17%) were the pathogens that were most frequently found. These results enhance knowledge of the pathogen microbes that may impact either humans or animals.